(3TQM GdbUjOI GdefaQLIs - (3CHh GdMSf Ydj Hf jhSa Hf Ydj GdHUQi GdTGaYjs; (3jhSa Hf eMeO Hf jhSa GdJhRQj , GdJdeSGfj, CHh GdaVd, GHf GdfMhqj,J (B513 (3g` s
(3ChdgG (B:s
(3hHYO aEf GdbUjOI GdeSeGI HGdefaQLI fXe GdEeGe GdYGQa GHddg CHh dGaGVd jhSa Hf eMeO Hf jhSa GdeYQha HGHf GdfMhi s
(3BNQgG (B:s
(3hgh QGVi YfG Gddge Mbb dfG Pdc jG cQje hGdMeO ddg QH GdYGdejf GfJgi s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B247 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B334s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs